Pengaruh Pertumbuhan Ekonomi, Angka Partisipasi Kasar, dan Laju Pertumbuhan Penduduk Terhadap Tingkat Kemiskinan di Kabupaten/Kota Provinsi Kalimantan Selatan Periode 2015-2019 - Adi Perkasa, Muhammad Murjani; Siregar, Syarituah (PPJP ULM, 2024)
This study aims to determine the effect of Economic Growth, Gross Participation Rate (SD, SLTP, SLTA), and Population Growth Rate on the Percentage of Poverty in Regencies/Cities of South Kalimantan Province. This research The method used in this study is panel data regression with a Fixed Effect Model (FEM) approach using E-Views 10 Software. The data used is secondary data panel (pooled data) which is a combination of time series data from 2015 to 2019 and cross section. The results of this study show that Economic Growth has a significant and positive effect on the percentage of poverty, the gross participation rate of elementary schools and high schools has an insignificant and negative effect on the poverty, and the population growth rate has an effect on the poverty, and the population growth rate has an effect significant and positive on the poverty.